Expression of ALCAM in Clinical Colon Cancer and Relationship With Patients’ Treatment Responses - FANG, ZIQIAN; ZENG, JIMMY JIANYUAN; YANG, YIMING; RUGE, FIONA; LANE, JANE; HARGEST, RACHEL; JIANG, WEN G. (In vivo (Athens), 2023)
Activated leukocyte cell adhesion molecule (ALCAM) plays an important role in cancer via its homotypical and heterotypical interactions with ALCAM or other proteins and can also mediate cell-cell interactions. The present study investigated the expression of ALCAM in relation to epithelial-to-mesenchymal transition (EMT) markers and its downstream signal proteins including Ezrin-Moesin-Radixin (ERM), in clinical colon cancer and in the progression of the disease. Expression of ALCAM was determined in a clinical colon cancer cohort and assessed against the clinical pathological factors and outcome, together with the expression patterns of the ERM family and EMT markers. ALCAM protein was detected using immunohistochemistry. Cell line models, with ALCAM knock-down and over-expression, were established and used to test cells' responses to drugs. Tumours from patients who had distant metastasis and died of colon cancer had low levels of ALCAM. Dukes B and C tumours also had lower ALCAM expression than Dukes A tumours. Patients with high levels of ALCAM had a significantly longer overall and disease-free survival than those with lower ALCAM levels (p=0.040 and p=0.044). ALCAM is not only significantly correlated with SNAI1 and TWIST, also positively correlated with SNAI2. ALCAM enhanced the adhesiveness of colorectal cancer, an effect inhibited by both sALCAM and SRC inhibitors. Finally, high ALCAM expression rendered cells resistant, especially to 5-fluorouracil. Reduced expression of ALCAM in colon cancer is an indicator of disease progression and a poor prognostic indicator for patient's survival. However, ALCAM can enhance the adhesion ability of cancer cells and render them resistant to chemotherapy drugs.